Analisis Framing Pemberitaan Thomas Lembong Pada Media Online Kompas.Com - Megi Ariansyah (Komsospol, 2025)
Abstract: Mass media is a means of conveying messages, ideas, and information to the public, which can be conveyed through news, content, or other discourse. The media's crucial role in conveying and disseminating information on an issue can shape and influence public opinion. Such as the issue of determining Thomas Lembong's suspect status, which has become a public spotlight because he is suspected of committing a criminal act of corruption in 2015 which caused losses to the state. The determination of Thomas Lembong's suspect status has become a legal issue reported by various media, such as the online news site kompas.com. This study aims to determine how the online media Kompas.com frames the news regarding the determination of Thomas Lembong's suspect status and to reveal how the news construction is formed through the news. The method used in this study is Robert N. Entman's framing analysis, which includes four elements: problem definition, problem identification, moral judgment, and resolution recommendations. The results show that Kompas.com's coverage of Thomas Lembong's suspect status tends to be neutral and places more emphasis on the legal aspects and the investigative process. The research results show that Kompas.com's coverage of Thomas Lembong's suspect status tended to be neutral, emphasizing the legal aspects and the investigative process. Therefore, this study concludes that the media constructs the reality of an event through reporting in accordance with its perspective and editorial policy. Keywords: Framing analysis Robert N. Entman, Online media, Thomas Lembong. Abstrak: Media massa merupakan sarana penyampaian pesan, ide, dan informasi kepada khalayak yang dapat disampaikan melalui berita, konten maupun wacana lainnya. Peran penting media dalam penyampaian serta penyebaran informasi terhadap suatu isu dapat membentuk dan mempengaruhi opini publik. Seperti halnya pada isu penetapan status tersangka Thomas Lembong yang menjadi sorotan publik karena diduga melakukan korupsi di tahun 2015 lalu hingga merugikan negara. Penetapan status tersangka thomas lembong ini menjadi masalah hukum yang diberitakan oleh berbagai macam media seperti dalam situs berita online kompas.com Penelitian ini bertujuan untuk mengetahui bagaimana media online Kompas.com dalam membingkai pemberitaan mengenai penetapan status tersangka terhadap Thomas Lembong serta mengungkap bagaimana konstruksi pemberitaan yang terbentuk melalui pemberitaan tersebut. Metode yang digunakan dalam penelitian ini adalah analisis framing Robert N. Entman yang mencakup empat elemen yaitu pendefinisian masalah, identifikasi masalah, penilaian moral dan rekomendasi penyelesaian. Hasil penelitian menunjukkan bahwa media Kompas.com, pemberitaan penetapan status tersangka Thomas Lembong cenderung netral dan lebih menekankan pada aspek hukum serta proses penyelidikan. Demikian, penelitian ini dapat disimpulkan bahwa media mengonstruksi realitas suatu peristiwa melalui pemberitaan sesuai dengan sudut pandang dan kebijakan redaksional media. Kata Kunci: Analisis framing Robert N. Entman, Media online, Thomas Lembong.